Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10

Which step in solving this equation is justified by the Commutative Property of Addition?
Given ⇒ 2(x − 4) + 6x = 9x − 10
Step 1 ⇒ 2x − 8 + 6x = 9x − 10
Step 2 ⇒ 2x + 6x − 8 = 9x − 10
Step 3 ⇒ 8x − 8 = 9x − 10
Step 4 ⇒ 8x − 8x − 8 = 9x − 8x − 10
Step 5 ⇒ 0 − 8 = x − 10
Step 6 ⇒ −8 = x − 10
Step 7 ⇒ −8 + 10 = x − 10 + 10***
Step 8 ⇒ 2 = x + 0
Step 9 ⇒ 2 = x

3 answers

step 1
How about step 2?
Step b
Similar Questions
    1. answers icon 3 answers
    1. answers icon 1 answer
  1. What is the minimum number of steps required to isolate x to solvethe equation 4x + 12 = 8? "Mi one step (P) two steps R) three
    1. answers icon 1 answer
  2. 21 of 2321 of 23 Items19:35 Question Consider the sequence of steps to solve the equation: 3(x − 4) + 5x = 9x − 36 Given ⇒
    1. answers icon 1 answer
more similar questions